Highly Conductive and Stable Naphthalenediimide-Based Organic Salt Cathode for Robust Lithium-Ion Batteries - Su, Xiangyu; Shan, Zixuan; Peng, Xuan; Chu, Jianyi; Jia, Zhihao; Kou, Yanan; Jiang, Min; Chen, Yuan (Nano-Micro Letters, 2026)
Organic lithium salts are promising cathode candidates for sustainable lithium-ion batteries (LIBs) due to their synthetic simplicity and environmental friendliness. However, their practical application is often thwarted by active material dissolution and sluggish redox kinetics, stemming from limited conjugation and deficient electronic conductivity. Herein, we report a naphthalenediimide-based lithium salt (NDI-OLi) designed with a robust π-conjugated structure and high aromaticity to enhance electronic transport. Experimental and theoretical studies reveal that the relatively high electronic conductivity, rapid reaction kinetics, and stable delocalized electronic geometry of the NDI-OLi cathode are key factors enabling sufficient coordination between carbonyl sites and lithium ions. As a result, the NDI-OLi electrode presents a high reversible capacity of 160 mAh g−1 at 0.1 A g−1, excellent rate performance (99.9 mAh g−1 at 8 A g−1), and exceptional cycling stability with 85% capacity retention after 5000 cycles at 1 A g−1. This work opens up new avenues for developing highly conductive and stable organic salt cathodes toward high-performance and durable LIBs. Highlights: 1 A naphthalenediimide-based lithium salt (NDI-OLi) featuring a stable π-conjugated structure and high aromaticity is proposed as a cathode, which facilitates relatively high electronic conductivity and rapid electron transfer. 2 Experimental and theoretical investigations reveal that the stable delocalized electronic geometry and fast reaction kinetics enable sufficient coupling between carbonyl sites and lithium ions, ensuring excellent energy storage performance. 3 The NDI-OLi electrode demonstrates superior rate capability and long-term cyclability (85% capacity retention after 5000 cycles), outperforming previously reported organic lithium salt cathodes.